Assessing the Impact of Stone Quarrying on Vegetation Cover in Kiyoora Kabale District. - Abaho, Amos (Kabale University, 2024)
The study assessed the impact of stone quarrying on Kiyoora, Kabale district vegetation cover. The objectives of the study were to find out the effects of stone quarrying on vegetation cover in Kiyoora and to assess the measures put in place to reduce the effects of stone quarrying on vegetation cover. The quadrant method was used to identify different plant species in the quarry area. Results revealed that female respondents were highly represented in the study and different plant species included 30 different species of shrubs and small trees, 10 species of grasses and herbaceous plants, and 20 species of pioneer species. The study concluded that there is a very big relationship between stone quarrying and vegetation cover. The study of the environmental effects of stone quarrying on vegetation cover in Kiyoora, Kabale District, reveals significant impacts on the local ecosystem. The primary findings indicate a reduction in vegetation diversity, soil erosion and degradation, dust deposition on plants, and alterations in water resources. Stone quarrying has led to a noticeable decrease in plant species diversity, particularly among grasses and herbaceous plants. This reduction undermines the ecological stability and biodiversity of the region. The study recommended sensitizing community members about the dangers of stone quarrying on vegetation cover.